Pelatihan Pembuatan Bahan Ajar dengan Aplikasi Sigil Software pada Materi Penyajian Data - Audra Pramitha Muslim; Ratulani Juwita; Zulfitri Aima; Haryono, Yulia; Melisha Apriliani (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The current development of digital technology requires the world of education to balance learning by using technology-based learning media. One of the learning media innovations that can be developed is in the form of technology-based teaching materials in the form of electronic modules (e-modules) assisted by Sigil software. This training in making teaching materials is applied to data presentation material, in which the material displays lots of pictures in the form of diagrams to present data so that it is easy to read and understand. This training was conducted with the target of mathematics teachers at SMPN 18 Padang. The purpose of this training is for teachers to be able to make teaching materials assisted by sigil software on data presentation material and other materials and teachers can use teaching materials that have been made in the learning process. The result of this training is that it can facilitate teachers to learn how to make teaching materials with the sigil application and they also understand and practice how to make these teaching materials as evidenced by the results of teaching material products made directly by the training participants.